2008
DOI: 10.1038/nbt1358
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of kinase inhibitor selectivity

Abstract: Kinase inhibitors are a new class of therapeutics with a propensity to inhibit multiple targets. The biological consequences of multi-kinase activity are poorly defined, and an important step toward understanding the relationship between selectivity, efficacy and safety is the exploration of how inhibitors interact with the human kinome. We present interaction maps for 38 kinase inhibitors across a panel of 317 kinases representing >50% of the predicted human protein kinome. The data constitute the most compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

61
2,130
2
18

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,200 publications
(2,245 citation statements)
references
References 31 publications
61
2,130
2
18
Order By: Relevance
“…Interestingly, in primary cell lysates, c-midostaurin recognized BTK (Supplementary Table S2, Figure 4B). Most of these kinase targets were also identified by midostaurin in a cellfree system (29). In control experiments, we were able to show that midostaurin and cmidostaurin inhibit growth of HMC-1.…”
Section: Drug Profiling Of Midostaurin In Neoplastic MC Reveals a Unimentioning
confidence: 75%
See 2 more Smart Citations
“…Interestingly, in primary cell lysates, c-midostaurin recognized BTK (Supplementary Table S2, Figure 4B). Most of these kinase targets were also identified by midostaurin in a cellfree system (29). In control experiments, we were able to show that midostaurin and cmidostaurin inhibit growth of HMC-1.…”
Section: Drug Profiling Of Midostaurin In Neoplastic MC Reveals a Unimentioning
confidence: 75%
“…However, midostaurin also interacts with other target-antigens, such as PDGFR, FLT3 and PKC (27,29). We asked whether the target-spectrum of CGP52421 differs from that of midostaurin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the results of this study are disappointing, over time the p38 inhibitors have become progressively more potent and selective (27). In addition, studies are ongoing in neuropathic pain, chronic obstructive pulmonary disease, atherosclerosis, and oncologic indications as well as in RA (28).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that examined the activity of sunitinib against a panel of 317 kinases (representing 450% of the known kinome) revealed that sunitinib has relatively high affinity for at least 40 other kinases, including myosin light-chain kinase, MEK1 and MEK2 (Karaman et al, 2008). As activation of multiple kinase-signalling pathways is a requirement for growth factor-mediated stimulation of angiogenesis, the relatively broad kinase substrate specificity of sunitinib might be expected to limit the potential for other growth factors to drive resistance to sunitinib through a mechanism that involves direct stimulation of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%